Guidelines for Drawing Causal Loop Diagrams - and Daniel H., Kim (The Systems Thinker, 1992)
The old adage “if the only tool you have is a hammer, everything begins to look like a nail” can also apply to language. If our language is linear and static, we will tend to view and interact with our world as if it were linear and static. Taking a complex, dynamic, and circular world and linearizing it into a set of snapshots may make things seem simpler, but we may totally misread the very reality we were seeking to understand. Making such inappropriate simplifications “is like putting on your brakes and then looking at your speedometer to see how fast you were going” says Bill Isaacs of the MIT Center for Organizational Learning. Articulating Reality Causal loop diagrams provide a language for articulating our understanding of the dynamic, interconnected nature of our world. We can think of them as sentences which are constructed by linking together key variables and indicating the causal relationships between them. By stringing together several loops, we can create a coherent story about a particular problem or issue.